1995
DOI: 10.1002/clc.4960181211
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery aneurysm: Review and case report

Abstract: Summary: Aneurysms involving the main pulmonary artery and its branches are rare. Clinical experience is limited and current knowledge is mainly derived from autopsy findings. This case report describes a patient with a pulmonary artery aneurysm associated with a previous, partially corrected stenotic pulmonary valve. The patient presented with symptoms suggestive of aneurysm dissection three decades after cornmissurotomy. The diagnostic approach and therapeutic intervention are emphasized with a review ofthe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 13 publications
0
68
0
4
Order By: Relevance
“…1,2,8 Pulmonary valve stenosis, including postvalvular stenosis, has frequently been described as an isolated cause of PAA formation. 5,9 In fact, early pulmonary valve commissurotomy in the patient's history may precipitate aneurysm formation because of an eccentric right ventricular outflow jet, which may lead to weakening of the vascular wall. 9 Furthermore, 1 case report described PAA formation in a patient presenting with the Noonan syndrome, a relatively common autosomaldominant congenital disorder that is also associated with pulmonary stenosis.…”
Section: Congenital Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,8 Pulmonary valve stenosis, including postvalvular stenosis, has frequently been described as an isolated cause of PAA formation. 5,9 In fact, early pulmonary valve commissurotomy in the patient's history may precipitate aneurysm formation because of an eccentric right ventricular outflow jet, which may lead to weakening of the vascular wall. 9 Furthermore, 1 case report described PAA formation in a patient presenting with the Noonan syndrome, a relatively common autosomaldominant congenital disorder that is also associated with pulmonary stenosis.…”
Section: Congenital Causesmentioning
confidence: 99%
“…5,9 In fact, early pulmonary valve commissurotomy in the patient's history may precipitate aneurysm formation because of an eccentric right ventricular outflow jet, which may lead to weakening of the vascular wall. 9 Furthermore, 1 case report described PAA formation in a patient presenting with the Noonan syndrome, a relatively common autosomaldominant congenital disorder that is also associated with pulmonary stenosis. 6 Many patients with PAA also present with pulmonary valve regurgitation, and even though it is more plausible that it is a consequence of annulus dilatation by the PAA, it may also be an independent etiologic factor in the formation of a PAA.…”
Section: Congenital Causesmentioning
confidence: 99%
“…A study published in 1947 by Deterling and Claggett reported the incidence of proximal pulmonary artery aneurysms was 1 in 14,000 post-mortem examinations at their center. 1,2 Congenital pulmonic valve stenosis is associated with pulmonary artery dilation, but true pulmonary artery aneurysm formation in this clinical situation is rarely reported in the literature. 3 Proximal pulmonary artery aneurysm is usually defined by one of two main criteria: the PA/aorta diameter ratio greater than 2 as seen on transthoracic echocardiography 3,2 or a pulmonary artery diameter of greater than either 4 cm 4,5 or 5 cm 3 .…”
Section: Schwalk Et Al Pulmonary Artery Aneurysm Secondary To Congenmentioning
confidence: 99%
“…Whether medial degeneration causes the dissection, predisposes to intimal tears, or is simply the result of chronically elevated intravascular pressure remains controversial. 47 Approximately 70 cases of PAD have been described, [43][44][45][46][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] of which almost 10 were diagnosed during life. 43,[65][66][67][68][69] Congenital heart disease was the underlying condition in the majority of cases, with the patent ductus arteriosus representing the most common defect.…”
Section: Pulmonary Artery Dissection and Rupturementioning
confidence: 99%
“…In a small number of cases, PAD may occur at the site of localized aneurysms, which are most common in congenital heart disease. 67 In contrast to aortic dissection, the false lumen in PAD tend to rupture rather than to develop a re-entry site. 68 PAR may occur into the pericardium [70][71][72] or pleural cavity, leading to sudden death, and usually involves the site of maximal diameter of the pulmonary artery.…”
Section: Pulmonary Artery Dissection and Rupturementioning
confidence: 99%